Efecto de analgesia multimodal para manejo del dolor postquirúrgico con tramadol-meloxican y ketoprofeno-metamizol en gatas sometidas a ovariohisterectomía - Delgado Zambrano, Issis Julieth (2024)
The effect of multimodal analgesia was evaluated to manage postsurgical pain in cats undergoing ovary hysterectomy with the use of drugs such as Tramadol + Meloxican and Ketoprofen + Metamizole. The ethological evaluation of the face was used through the digital application “Feline Grimace Scale” (FGS) and the measurement of physiological constants such as Respiratory Rate (RR), Heart Rate (HR), Temperature (T°), Systolic Blood Pressure (SBP) , Mean arterial pressure (MAP) and Diastolic blood pressure (DBP) to evaluate the postsurgical analgesic response; For those variables with a normal distribution, the Student T test was applied, otherwise the Man-Whitney test was used. The results showed that T1 (Tramadol + Meloxican) provided greater pain relief compared to T2 (Ketoprofen + Metamizole). In addition, significant differences (p<0.05) were found, since in the first treatment the RR 30.4±6.56, HR 155.93±8.8, SBP 144.87±6.75, DBP 85.93±6.52, MAP 125.67±8.68 and T° 38.64±0.58 are lower values than those obtained by the second treatment, which in this case are RR 36±4.78, HR 182.87±11.64, SBP 171.07±7.51, DBP 90±4.78, MAP 138.13±5.95 and T° 38.79±0.41. This means that T1 does provide postoperative analgesia and contributes to animal well-being. Thus, concluding that the use of multimodal analgesia for pain management with the use of the Tramadol + Meloxicam protocol complies with the analgesic triad.